Effect of Replacing Oil Seed Cakes with Rice Dried Distiller’s Grains with Solubles in Concentrate Mixture on Growth and Nutrient Utilization in Murrah Heifers - Singh, S.K.; Thakur, S.S.; Yogi, R.K.; ud-deen, Asgar (Indian Journal of Animal Nutrition, 2018)
The present experiment was carried out to study the effect of replacing oil seed cakes (ground nut cake and mustard oil cake) with rice dried distiller’s grain with solubles (RDDGS) at 50 and 75% level (on CP basis) in concentrate mixture on growth performance, nutrient utilization and some blood parameters in Murrah heifers. Eighteen Murrah heifers (12-20 month age; Av. BW= 196 kg) were allocated to three groups of six animals on the basis of body weight and age. All the animals were offered diet consisting of wheat straw, green fodder and concentrate mixture. The concentrate mixture in Control group contained maize grain, de oiled rice bran, wheat bran, barley, ground nut cake, mustard oil cake, mineral mixture and salt (22, 15, 15, 10, 25, 10, 2 and 1 parts, respectively). The animals in group T1 and T2 were fed on diet containing concentrate mixture in which ground nut cake and mustard oil cake was replaced with rice DDGS at 50 and 75% level, respectively on CP basis. A growth trial was conducted for 90 days. There was no difference in intakes of DM, CP, TDN, digestibility of nutrients, nitrogen retention and haemato-biochemical parameters except plasma urea nitrogen which decreased (P<0.05) with increasing levels of rice DDGS in the diets. Feed cost per kg gain/animal was reduced by `14.90 and 13.27 at 50 and 75% level of replacement of oil seed cakes with rice DDGS. Hence, rice DDGS could be used as an alternative protein sources replacing up to 75% of oil cakes (GNC and MOC) on CP basis in concentrate mixture of Murrah heifers.